Associations of Triglyceride-Glucose Index and Its Derivatives with Hyperuricemia Risk: A Cohort Study in Chinese General Population. (17th September 2020) - Gu, Qing; Hu, Xue; Meng, Jian; Ge, Jun; Wang, Sui Jun; Liu, Xing Zhen
Abstract : Background . Identification and intervention of insulin resistance may be beneficial to the prevention of hyperuricemia (HUA) and its related diseases. Thus, we conducted this longitudinal study to examine the relation of triglyceride-glucose index (TyG), a simple noninsulin-based IR assessment tool, and its derivatives with the risk of HUA. Methods . A total of 42, 387 adults who received routine health screening and were free of HUA were included for the longitudinal analyses. TyG, body mass index (BMI), waist circumference (WC), and waist-to-height ratio (WtHR) were calculated through anthropometric and biochemical indicators. Associations of TyG, TyG-BMI, TyG-WC, and TyG-WHtR with HUA risk were estimated using Cox regression analyses. Results . The incident cases of HUA occurred in 4, 230 subjects during the 138, 163 person-years of observation, and the crude incidence rate of HUA was 30.6 per 1000 person-years. After multivariate adjustment, we observed an increased risk for incident HUA for the upper TyG and its derivatives' tercile. The HRs of TyG were greater than that of its components in both sexes. Compared with TyG, TyG-related parameters only had higher HRs in women but not in men. Conclusions . TyG and its integration with obesity indicators have the potential to help risk stratification and prevention of HUA, especially among women.